The Influence Of The Board of Supervisors, Commissioners, and the Audit Committee To The Islamc Social Reporting With The Size of Company as a Moderation Variable - Yessy Anggriani,; Iwan Fakhruddin,; Ani Kusbandiyah,; Bima Cinintya Pratama, (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
The protection for costumers fund deposited at the bank is a crucial aspect within the relationship between the bank and costumers. This is very important considering that costumers’ money is susceptible to a number of threats such as illegal practices by bank’s employees themselves or other parties through a variety of methods. This research aims at assessing the influence of the Board of Supervisors within the Sharia Bank, the Board of Commissioners, and the Committee of Auditing to Islamic Social Reporting. This research employs the company size as the moderation variable. The population and data used cover 15 general sharia banks registered at the OJK (the Indonesian Authority for Financial Service) in 2015 with 86 observation points. The analysis methods applied in the research are classical assumptions and regression test with Stata. The findings of the research indicate that the size of the Sharia Supervisor Board and the Sharia Supervisor Board Meeting with measurement moderation has positive impacts to the Islamic Social Reporting. The Islamic Social Reporting is very significant to ensure the companies comply to the sharia rules, to increase stakeholder trusts, to manage risks, and to support sustainable social and economic development.